A review on kiln system modeling - Saidur R.; Hossain M.S.; Islam M.R.; Fayaz H.; Mohammed H.A. (2023)
The purpose of this study is to evaluate performance cement of production and cement kiln. The design of energy efficient dryers employing heat pump systems and the dynamic response of the product to the kiln conditions must take into account. In this paper, the formulation of a dynamic and kiln-wide drying model is described. The model predictions have been verified by comparing them with the published experimental data. The model is then used to simulate performance of three industrial kilns. Numerical experiments are carried out to investigate influence of key operating and design parameters on energy consumption of kilns. The model is also used to explore the possibility of manipulating temperature profile within the kiln to reduce energy consumption per tonne of clinker. Cement kiln dust is a fine-grained material produced during the manufacture of cement. At present reuse option is limited and the bulk of cement kiln dust that is not reused in the cement manufacturing process is sent to landfills or stored on-site. Due to the calcium oxide (CaO) content of cement kiln dust, it has the potential to be used as a replacement for lime in treating acidic wastewaters such as acid rock drainage. Slaking of two of the cement kiln dust samples with the highest free lime contents (e.g., 34% and 37% free of CaO) gave elevated pH values statistically comparable to those of the commercial quicklime sample that was characterized as having 87% of CaO. Acid neutralization trials indicate that cement kiln dust samples with low free lime contents could be effective at neutralizing acidic wastewaters. 2011 Elsevier Ltd. All rights reserved.